Bio-Based PLA Membranes for Ion Transport and Ion Filtration - Sriram, M.; Kathirnilavan, R.S.; Mohammed, K. Ashick Naina; Kumar, S. Ananda; Mishra, Anshuman; Tiwari, Ashutosh (Journal of Research Updates in Polymer Science, 2023)
Lithium-ion batteries require battery separators for both safety and electrochemical performance. Due to that, they have received a lot of attention. In order to prevent any electronic current from moving within the negative and positive electrodes and allow ions to flow through while avoidance of electric contact between them, a porous membrane used as a separator is positioned between the electrodes with opposing polarities. Accordingly, the objective of the present work is to build a biodegradable PLA based battery separator, which has exceptional thermal capabilities and can endure temperatures of up to 300°C. They also seem to serve as the least degree of barrier for the flow of an ionic current. In this study bio-polymer battery separator membranes were developed using PLA as matrix material and fillers such as Copper slag (CS) and Cardanol resin (CNSL). CS and CNSL were preferred for the reason to realize the concept of a wealth reclaimed from wastes that act as toughening and pore forming agent for PLA matrix. It is found that at PLA-CS film has more brittleness when compared to neat PLA and PLA-CNSL resin. On the other hand, PLA-CNSL films are the toughest ones. Overall, it has been demonstrated that obtaining more sustainable and high-performance is possible by the usage of such sustainable materials for futuristic developments.